Anteseden Peningkatan Kinerja Pegawai Kantor Perbekel - Anggi, Ni Made; Astrama, I Made; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Performance is all the results that have been achieved by employees. To achieve optimal performance, many influencing factors include: Quality of work life, Self efficacy and Motivation. The purpose of this study was to determine how the influence of Quality of Work Life, Self efficacy on performance either directly or through the mediation of motivation. This research was conducted at the Selat Perbekel Office, Kec. Abiansemal, Kab. Badung. The number of samples taken were 30 respondents. The data collection techniques are observation, interviews, and questionnaires, while the data analysis technique is path analysis and Sobel test to determine the role of mediating variables. The results showed that quality of work life, self-efficacy, and motivation had a positive and significant effect on employee performance, quality of work life and self-efficacy had a positive and significant effect on motivation. The results of the mediation test prove that motivation mediates the effect of quality of work life and self-efficacy on employee performance.